2007
DOI: 10.1002/ibd.20100
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab treatment influences the serological expression of matrix metalloproteinase (MMP)-2 and -9 in Crohnʼs disease

Abstract: Infliximab treatment increases MMP-2 and decreases MMP-9 in serum of patients with CD, the latter also in the intestine, which extends and confirms our previous ex vivo explants observations. However, these changes were not strictly associated with the response to treatment. The enhanced leukocyte MMP-9 expression in CD seems to be regulated by TNF-alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 52 publications
2
41
0
2
Order By: Relevance
“…It has been demonstrated that TNF-␣ is important in the pathogenesis of inflammatory bowel disease, and inhibition of TNF-␣ results in alteration of MMP2 and MMP9 levels in CD patients (Podolsky, 2002;Gao et al, 2007). Therefore, we detected the expression of TNF-␣ and the effect of mesalamine on TNF-␣-regulated MMP2 and MMP9 in the experimental UC.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…It has been demonstrated that TNF-␣ is important in the pathogenesis of inflammatory bowel disease, and inhibition of TNF-␣ results in alteration of MMP2 and MMP9 levels in CD patients (Podolsky, 2002;Gao et al, 2007). Therefore, we detected the expression of TNF-␣ and the effect of mesalamine on TNF-␣-regulated MMP2 and MMP9 in the experimental UC.…”
Section: Resultsmentioning
confidence: 94%
“…Kaiser et al (1999) demonstrated that 5-ASA blocked TNF-␣ activation in mouse colonocytes. This finding indicated that restored balance between MMP2 and MMP9 by 5-ASA in UC might be mediated by reduction of TNF-␣, as demonstrated by Gao and his colleagues that inhibition of TNF-␣ increases MMP2 and decreases MMP9 in patients with Crohn's disease (Gao et al, 2007). In addition, another study demonstrated that stimulation of CaCO-2 cells with TNF-␣ led to a dosedependent increase in expression and secretion of MMP9 (Gan et al, 2001).…”
Section: Mesalamine Restores Angiogenic Balance In Ulcerative Colitismentioning
confidence: 79%
See 1 more Smart Citation
“…PF4 is generally found angiostatic, prothrombotic, acts as inhibitor of immune cell migration elicited by other chemotactic cytokines and is able to induce leukocyte activation. It could be part of a complex mechanism of control of tissue healing and infiltration also involving Matrix Metallo-Proteinases (MMP-2 and 9), highlighted in a recent study addressing as well the characterization of infliximab's mode of action in CD [17]. PF4 is also considered as an acute phase reactant because its level increases with general inflammation, as already observed in plasma of CD patients [18][19][20].…”
Section: Discussionmentioning
confidence: 96%
“…Biomarkers showing a significant evolution in at least 4/10 patients in R were different from those in NR patients, highlighting different modifications in serum composition depending on the response to infliximab. The identification of these markers should provide new information about infliximab's mode of action and could be other components of the complex mechanism leading to infiltration, tissue remodelling and to healing, already known to involve specific MMPs [17]. The expressions of these proteins are, like PF4 and other "CXC" chemokines, also controlled by proinflammatory cytokines and are produced in their final mature and active form(s) by proteolytic processing.…”
Section: Discussionmentioning
confidence: 99%